Effect of Activation Temperature and H3PO4 Concentration on Activated Carbon from Asian Palmyra Palm Fronds (Borassus Flabellifer Linn) - Rini, Dwi Sukma; Prasetyo, Dhimas Mardyanto; Adawi, Turmiya Fathal; Aji, Irwan Mahakam Lesmono; Syaputra, Maiser; B, Kornelia Webliana; Ningsih, Rima Vera (Jurnal Multidisiplin Madani, 2024)
Asian palmyra palm (lontar) fronds are a byproduct generated from the asian palmyra palm plant. To add value to these fronds, they can be converted into activated charcoal. This study aims to determine the properties of activated charcoal derived from asian palmyra palm fronds and the effects of activation temperature and chemical concentration on these properties. The activation process was conducted using H3PO4 solution with two concentration variations, 10% and 20%, for 24 hours, and three temperature variations, 600°C, 700°C, and 800°C, each for 60 minutes. The data obtained were analyzed using R software version 4.3.1. The effects of the variation factors in H3PO4 concentration and activation temperature on the yield and characteristics of the activated charcoal were calculated using two-way ANOVA with a 95% confidence level. The properties of the activated charcoal produced met the SNI 06-3730-1995 standard for technical activated charcoal, with yield, moisture content, ash content, volatile matter content, fixed carbon content, and iodine adsorption values of 80.41%, 0.42%, 9.35%, 8.28%, 82.38%, and 668.13 mg/g, respectively. The best properties of activated charcoal were obtained from the activation treatment at 600°C and 20% H3PO4 concentration